2006
DOI: 10.1097/00006982-200602000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Toxicity of Moxifloxacin

Abstract: Intravitreal injection of moxifloxacin at a concentration of < or =160 microg/0.1 mL appeared nontoxic in the rabbit eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 18 publications
1
23
1
1
Order By: Relevance
“…Intravitreal injections have emerged during the last years as a new very effective way for delivering therapeutic agents intraocularly [23][24][25], ameliorating the possible systemic effects of such agents. However, intravitreal administration poses also risks related both to the procedure of administration [26] and to the local toxicity of the various administered agents [27].…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injections have emerged during the last years as a new very effective way for delivering therapeutic agents intraocularly [23][24][25], ameliorating the possible systemic effects of such agents. However, intravitreal administration poses also risks related both to the procedure of administration [26] and to the local toxicity of the various administered agents [27].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study showed that at concentrations higher than 160 g/ml, moxifloxacin induced adverse effects on primary RPE and neuronal retinal cells with regard to cell proliferation and cell viability [29] . Further studies in vivo showed that intravitreal injection of moxifloxacin did not cause retinal toxicity up to 100 g/ml in mice or 150 g in rabbits [30] . In vivo, intravitreal injection of the other quinolone, gatifloxacin, at doses varying from 50 to 400 g, caused no retinal toxicity, assessed clinically and microscopically in rabbits [30] .…”
Section: Quinolonesmentioning
confidence: 96%
“…Further studies in vivo showed that intravitreal injection of moxifloxacin did not cause retinal toxicity up to 100 g/ml in mice or 150 g in rabbits [30] . In vivo, intravitreal injection of the other quinolone, gatifloxacin, at doses varying from 50 to 400 g, caused no retinal toxicity, assessed clinically and microscopically in rabbits [30] .…”
Section: Quinolonesmentioning
confidence: 96%
“…The safety of ocular (topical and/or intra-vitreal) administration of ofloxacin [10][11][12], ciprofloxacin [10], evofloxacin [13], norfloxacin [14], trovafloxacin [15], moxifloxacin [16] and garenoxacin [17] has been investigated, and the results lead to the conclusion that FQs show varied affinity for retinal tissues and there are a marked differences among compounds for safe doses for ocular administration.…”
Section: Introductionmentioning
confidence: 99%